순천 국제생태정원박람회 유치·개최 타당성 조사 - 석현덕 (한국농촌경제연구원, 2009)
The purpose of this study is to verify an economic feasibility of the International Garden Exposition which will be hold at Suncheon, Jeonllanamdo in 2013. Main contents of the study consist of regional conditions and competitive power of the city of Suncheon, estimation of visitors, analysis of economic feasibility, and estimation of regional economic effects. According to the estimation, a gross of domestic visitors ranges from 3.96 millions to 4.68 millions. Among them, adult visitors over age 18 range from 3.27 to 3.74 millions people. An optimal level of foreign visitors was estimated from 58,557 to 223,073 people. The result of economic feasibility showed that BCR was above 1.0(from 1.054 to 1.239) regardless of changes of all the conditions. All the sensibility analysis were conducted by the way of changing amount of admission fees, government subsidies and visitors. In regional economic effects of whole country, as 22.1 billions won by construction investments, 20 billions won by consumer spendings for exhibition, and 345.7 billions won(nation visitor 250.9 billions won and foreign visitors 94.7 billions won) by visitors are invested, a gross production of 1,332.3 billions won, value-added of 679 billions won, and jobs of 10,793 will be created. In the local area, a gross production of 7,536 billions won, value-added of 407.8 billions won, and jobs of 7,106 will be induced. In conclusion, The results of the study show that holding the International Garden Exposition at Suncheon in 2013 will be feasible economically and politically.